Estudio de prefactibilidad para la confección y comercialización de artículos textiles en línea infantil para la empresa inversiones textiles 2G s.a.s. (2022)
The incursion of any company in a new market is full of uncertainties, which means that there is a high risk when making the investment, the objective of this project is related to the production and marketing of online children's clothing, garments clothing are a variable product due to the large number of elements with which they are related such as fashion, trends, climate that are changing aspects, that is why the pre-feasibility study was carried out by conducting market, technical, environmental studies and financial in order to minimize investment risks.